Origin, extent, and emplacement conditions of newly exposed pillow lavas in the Kverkfjöll region, Iceland - field photos and thin sections - Iðunn Kara Valdimarsdóttir (Zenodo, 2023)
Fieldwork photos from Kverkfjöll, Iceland, since 2020 as a part of fieldwork-based master's thesis in geology, where a pillow lava and hyaloclastiteformationwasstudied.Included are field photos and composited field photos, along with a map showingwhere said photos are. Also included are photomicrographs of thin sections, scanned and labeled photos of eachthin section, andtheir rough position within each pillow crust sample. Please refer to the actual thesis for more information: Origin, extent, and emplacement conditions of newly exposed pillow lavas in the Kverkfjöll region, Iceland (Valdimarsdóttir, 2023).